Factibildad para la creación de un hotel en la Parroquia Chito, Cantón Chinchipe, Provincia de Zamora Chinchipe - Urrego Jiménez, Jhoana Elizabeth (2017)
This project entitled "FEASIBILITY FOR THE CREATION OF A HOTEL IN CHITO PARK, CANTÓN CHINCHIPE, PROVINCE OF ZAMORA CHINCHIPE", proposes the idea of investing in the creation of a Hotel as a solution to the problem of lack of infrastructure, ( Hotels) in the Chito parish. The main objective of the research is to carry out a feasibility study for the creation of a hotel in the Chito parish. With the creation of this hotel, it is intended to promote the tourism of this parish, thus generating more sources of employment and encouraging tourism. For the structuring and development of the research project it was necessary to apply different methods and techniques which helped the development of the same in different aspects such as the realization of the referential framework of the topic raised, from interviews and personal surveys, to achieve generalizations behaviors or skills Among the actors of the tourist activity, the analysis of the results obtained in the market study was also carried out, allowing to recognize and determine the tastes and preferences of the clients and other characteristics, in which they should be based to offer their tourist services and Finally we were able to perform calculations corresponding to the financial analysis and financial study. The market segment established the market segment to which services will be directed, tourists visiting the Chito parish in the period 2016 (815 tourists). Currently 84% of this demand is using tourism services (684 tourists); However, of this percentage 100% is really interested in making 7 use of the service offered (684 tourists). THE HOTEL SAN ANTONIO CIA. LTDA will be located in the Chito parish, Chinchipe Canton, Province of Zamora Chinchipe. The installed capacity of the project was determined based on the facilities that the hotel will have to attend to its clientele will have a capacity of 6,656 people annually. The processes to be performed for the provision of services by area were determined: in the area of accommodation the estimated time to provide a service unit is 12 minutes if the reservation is made via internet or telephone and 10 minutes if done personally . The facilities of the company were established according to the service that will offer the hotel; In addition, the distribution of the plant by service area was determined. The Company to be created will be constituted under the name of limited liability, that is to say, HOTEL SAN ANTONIO CIA.LTDA., Integrated of 10 shareholders with the contribution of the partners of $ 98,598.33 (50%) and the other 50% creadito to the Corporation Financial. An investment budget was calculated, with the objective of determining the requirement of the necessary assets that will allow the hotel to provide its services, fixed assets with a total investment of $ 192,175.60, deferred assets: with a total of $ 2,055.00, current assets a Working capital of $. 4.367, 74 in essence the project will require a total investment of $ 198,598.33. It will be carried out with a 50% equity and the other 50% credit to the Finance Corporation. The costs were determined based on the requirements to provide the services, in which the most influential costs are the prime costs made up of direct labor. The costs were projected for the 8 10-year life of the project. For the calculation of the income it was necessary to obtain results of the unit costs per unit of service, where it was possible to establish a profit margin to determine the retail price of the tourist products. It was determined the unit price of the service for year 1 is $ 15.00. With the Statement of Profit and Loss it was possible to know if the company will incur future losses or profits, the present state showed positive balances, for year 1, a profit of $ 99,840.00 was budgeted. The calculation of the break-even point was done in terms of installed capacity and sales. The cash flow allowed us to anticipate that the company in the future will not get a cash deficit to cover its income and expenses. For the 1 year, a result of $ 31,332.43 was obtained. The calculation of the NPV facilitates the delimitation of the return on investment, ie the hotel will earn $ 688.03 over the 10-year project life span. The IRR of the project is 9.21%. In calculating the Cost Benefit Ratio indicator, it was concluded that for each dollar invested in this project, it would earn 60 cents. With respect to the increase in costs the project supports until 21.80, therefore has a sensitivity of 0.99 and from that point of view the project is not sensitive and therefore can be executed. In terms of revenue, the project supports the 13.50% decrease, giving a sensitivity of 0.90, which means that the project is not sensitive and can be executed. Finally in the period of capital recovery will be done in a Term of 7 years, 3 months and 29 days.Finally, it is concluded that the present project is feasible and will constitute a very beneficial form of investment for the investors, since the profits to be obtained will be profitable during .